Fabrication of Novel g-C3N4@Bi/Bi2O2CO3 Z-Scheme Heterojunction with Meliorated Light Absorption and Efficient Charge Separation for Superior Photocatalytic Performance - Hongxia Fan; Xiaohui Ma; Xinyang Li; Li Yang; Yongzhong Bian; Wenjun Li (Molecules, 2022)
Herein, a novel g-C3N4@Bi/Bi2O2CO3 Z-scheme heterojunction was synthesized via simple methods. UV/Vis diffuse reflectance spectroscopy (DRS) revealed that the visible light absorption range of heterojunction composites was broadened from 400 nm to 500 nm compared to bare Bi2O2CO3. The XRD, XPS and TEM results demonstrated that metal Bi was introduced into g-C3N4@Bi/Bi2O2CO3 composites, and Bi may act as an electronic bridge in the heterojunction. Metal Bi elevated the separation efficiency of carriers, which was demonstrated by photocurrent and photoluminescence. The performance of samples was assessed via the degradation of Rhodamine B (RhB), and the results exhibited that g-C3N4@Bi/Bi2O2CO3 possessed notably boosted photocatalytic activity compared with g-C3N4, Bi2O2CO3 and other binary composites. The heterojunction photocatalysts possessed good photostability and recyclability in triplicate cycling tests. Radical trapping studies identified that h+ and •O2− were two primary active species during the degradation reaction. Based on the energy band position and trapping radical experiments, the possible reaction mechanism of the indirect Z-scheme heterojunction was also proposed. This work could provide an effective reference to design and establish a heterojunction for improving the photocatalytic activity of Bi2O2CO3.